The Role of Psychological Empowerment Mediation and Organizational Commitment to Influence Transformational Leadership on Nurse Performance (Study at The Countermeasures Referral Hospital Certain Emerging Infectious Diseases in Bali) - Udayana, I Made; Supartha, Wayan Gede; Dewi, I Gusti Ayu Manuati; Sintaasih, Desak Ketut (Migration Letters, 2023)
Nurses who work during the pandemic have a high risk of exposure to the Covid-19 disease. The professional obligations of nurses that must be carried out during the pandemic have caused many nurses to have concerns about work and have an impact on their performance. This study aims to be able to analyze the role of psychological empowerment mediation and organizational commitment on the influence of transformational leadership on the performance of nurses in the isolation room of a referral hospital for the management of certain emerging infectious diseases in Bali. The sample of this study was 199 respondents from 396 nurses who worked in the isolation treatment room of a referral hospital to manage certain emerging infectious diseases in Bali. The sampling technique used is incidental sampling. This study uses a quantitative approach associative of causality with the dissemination of google form questionnaires analyzed using SmartPLS. The results of the study prove that (1) transformational leadership does not have a direct effect on nurse performance, (2) transformational leadership has a positive and significant effect on psychological empowerment, (3) transformational leadership has a positive and significant effect on organizational commitment, (4) psychological empowerment has a positive effect. and significant effect on nurse performance, (5) organizational commitment has a positive and significant effect on nurse performance, (6) psychological empowerment fully mediates positively and significantly influences transformational leadership on nurse performance, (7) organizational commitment fully mediates positively and significantly influences transformational leadership on nurse performance. Organizational commitment has a stronger mediating role than psychological empowerment on the influence of transformational leadership on nurse performance. This research implies that nurses’ performance improvement can be done with transformational leadership which is able to make nurses have high organizational commitment and psychological empowerment.